Usefulness of 1-hour and 24-hour heart rate holter inbuilt in new tx rate adaptive pacemakers. - Sermasi S; Marconi M; Marzaloni M (Pacing & Clinical Electrophysiology, 1990)
The rate adaptive TX* pacemaker uses the evoked QT interval as an indicator of physiological demand. In order to obtain a rate adaptation close to physiological patterns we used in the past, in each patient, on the slope value and/or the T wave sensing window, controlling via exercise stress testing and Holier the results achieved. It was an expensive method, but the system produced effective rate responsive pacing. The new series of TX* pacemakers (Quintech 919 and Rhythmyx), beside the dynamic slope feature, are equipped with a 1-hour heart rate Holter (HRH) that can he used during effort without the need for manually recording the heart rate. In this mode TX* pacemakers calculate the average heart rate over 20-second periods and stores the values continuously for 1 hour. In addition, a 24-hour HRH is available, which calculates the average heart rate over 7.5-minute periods. showing heart rate trend during the last day prior to interrogation. Each HRH can he accessed by the programmer and printed out. Using four Quintech 919* and five Rhythmyx units, the inbuilt HRH proved its utility by making the heart rate adaptation checking procedure easier, faster, and more economic.